Comparative Analysis Between Two Reliability Models of a Three-Unit Complex Industrial System - Syed Zegham Taj; Syed Mohammed Rizwan (Journal of Multidisciplinary Applied Natural Science, 2024)
A comparative analysis between two reliability models of a three-unit complex industrial system has been presented in this paper. Previously, real failure-maintenance data of a three-unit complex industrial system were collected. The situations depicted in the data were used for developing two appropriate reliability models for the system. Important reliability indicators of the system were estimated by applying Semi-Markov and regenerative processes. Here, a comparison between the reliability indices and profits of the two models is performed, which helps in identifying the suitability of one model over the other. Cut-off points for profits based on costs, revenues, and failure rates have also been obtained for deciding which of the two models is more profitable. Graphical analysis is also presented to illustrate the outcomes.